PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN PETA KONSEP (MIND MAPPING) DI SDN 13 KASSI KABUPATEN PANGKEP - Nurlaela Nurlaela; Muh. Yunus; Elpisah Elpisah (Institut Pendidikan Tapanuli Selatan, 2023)
This study aims to determine the increase in student learning outcomes through the application of a mind mapping learning model at SDN 13 Kassi, Pangkep Regency. The research subjects were 32 students of class V. The data collection technique used is observation and giving tests. The data analysis techniques were carried out qualitatively and quantitatively. The results of this study indicate that the increase in student learning outcomes through the application of the concept map learning model (mind mapping) at SDN 13 Kassi Pangkep Regency, namely that student learning outcomes have increased in cycle I by 66% (21 students who complete) and tends to be in the high category with a percentage of 56.3%, then it increased again in cycle II to 94% (30 students who completed) and tended to be in the high category with an increase in percentage of 62.5%. Therefore, through the concept map learning model carried out during cycle activities, it has been proven to improve student learning outcomes.